False Hope: A Bioethics Case Study - Martin, Ariana (Archives of Evidence-Based Medicine, 2023)
This text portrays the case study of a newborn who was diagnosed with gastroschisis, a congenital structural defect of the abdominal wall. The narrative explores the ethical questions raised by the complications of this case, focusing on three key issues: the bioethics principle of beneficence, patient transfer guidelines and parent decision-making capacity. The conclusion highlights the tension between parental autonomy and the potential for harm to the child, citing the parens patriae doctrine and the Harm Principle as possible grounds for state intervention in the United States. Overall, the text highlights the complexity of ethical considerations in medical cases involving children and calls for individual analysis and collaboration among healthcare professionals to find optimal solutions.